Pendampingan Pembuatan Lembar Kerja Peserta Didik (LKPD) Matematika Berbasis Model Pembelajaran Inquiry Pada Guru-Guru Matematika - Bhoke, Wilibaldus; Wangge, Maria Carmelita Tali; Bela, Maria Editha; Wewe, Melkior; Lola, Teofania Kristina; Wea, Marselina (Abdimas Indonesian Journal, 2024)
One of the concrete elements that is very important in efforts to improve the quality of human resources is improving the quality of education. However ini reality, teachers do not develop the creativity to plan, prepare, and create mature teaching materials that are rich in innovation so that they are attractive to students. Most mathematics learning activities only present problems and formulas without paying attention to the concepts embedded. The method of this assistance is delivering material on how to make Mathematics LKPD bsed on the inquiry learning model. In this case, the companion discusses the main things that must be considered before making the LKPD. Namely the objectivies of the learning itself which contains the content of the teaching material in making the LKPD that is linked to mathematics learning which is expected to be understandable for students.